Impact of COVID-19 vaccination on the use of PD-1 inhibitor in treating patients with cancer: a real-world study - Yang Yang; Junping Yin; Jian Li; Bo Liu; Ming Li; Qiao Huang; Xianglin Yuan; Christian Kurts; Guangyuan Hu; Qi Mei; Xi Tang; Alexander Böhner; et al. (Journal for ImmunoTherapy of Cancer)
Anti-COVID-19 vaccination may have functional implications for immune checkpoint inhibitor treatment in patients with cancer. This study was undertaken to determine whether the safety or efficacy of anti-PD-1 therapy is reduced in patients with cancer during COVID-19 vaccination. A large multicenter observational study was conducted in 83 Chinese hospitals between January 28, 2021 and September 30, 2021. A total of 3552 patients were screened and 2048 eligible patients with cancer receiving PD-1 inhibitor treatment were recruited. All enrolled patients had received camrelizumab treatment alone or in conjunction with other cancer therapies. Among these, 1518 (74.1%) patients received the BBIBP-CorV vaccine and were defined as the vaccinated subgroup. The remaining 530 (25.9%) patients did not receive anti-COVID-19 vaccination and were defined as the non-vaccinated subgroup. For all participants, Response Evaluation Criteria in Solid Tumor and Common Terminology Criteria for Adverse Events criteria were used to evaluate the efficacy and safety of camrelizumab treatment, respectively. Propensity score match analysis with the optimal pair matching was used to compare these criteria between the vaccinated and non-vaccinated subgroups. A total of 2048 eligible patients with cancer were included (median age 59 years, 27.6% female). Most patients (98.8%) had metastatic cancer of the lung, liver or intestinal tract. Aside from the PD-1 inhibitor treatment, 55.9% of patients received additional cancer therapies. 1518 (74.1%) patients received the BBIBP-CorV vaccine with only mild side effects reported. The remaining patients did not receive COVID-19 vaccination and had a statistically greater percentage of comorbidities. After matching for age, gender, cancer stage/types, comorbidity and performance status, 1060 patients (530 pairs) were selected for propensity score match analysis. This analysis showed no significant differences in overall response rate (25.3% vs 28.9%, p=0.213) and disease control rate (64.6% vs 67.0%, p=0.437) between vaccinated and non-vaccinated subgroups. Immune-related adverse events (irAEs) were reported in both subgroups after camrelizumab treatment. Among vaccinated patients who experienced irAEs, the median interval between the first dose of camrelizumab treatment and the first vaccine shot was ≤16 days. Compared with the non-vaccinated subgroup, irAEs in vaccinated patients were more frequently reported as mild (grade 1 or 2 irAEs; 33.8% vs 19.8%, p<0.001) and these patients were less likely to discontinue the PD-1 inhibitor treatment (4.2% vs 20.4%, p<0.001). Severe irAEs (grade 3 irAE or higher) related to camrelizumab treatment were reported, however no significant differences in the frequency of such events were observed between the vaccinated and non-vaccinated subgroups. The COVID-19 vaccine, BBIBP-CorV, did not increase severe anti-PD-1-related adverse events nor did it reduce the clinical efficacy of camrelizumab in patients with cancer. Thus, we conclude that patients with cancer need not suspend anti-PD-1 treatment during COVID-19 vaccination.